TEMPO Monolayers on Si(100) Electrodes: Electrostatic Effects by the Electrolyte and Semiconductor Space-Charge on the Electroactivity of a Persistent Radical. - Zhang, L.; Vogel, Y.; Noble, B.; Gonçales, V.; Darwish, N.; Brun, A.; Gooding, J.; Wallace, G.; Coote, M.; Ciampi, Simone (American Chemical Society, 2016)
This work demonstrates the effect of electrostatic interactions on the electroactivity of a persistent organic free radical. This was achieved by chemisorption of molecules of 4-azido-2,2,6,6-tetramethyl-1-piperdinyloxy (4-azido-TEMPO) onto monolayer-modified Si(100) electrodes using a two-step chemical procedure to preserve the open-shell state and hence the electroactivity of the nitroxide radical. Kinetic and thermodynamic parameters for the surface electrochemical reaction are investigated experimentally and analyzed with the aid of electrochemical digital simulations and quantum-chemical calculations of a theoretical model of the tethered TEMPO system. Interactions between the electrolyte anions and the TEMPO grafted on highly doped, i.e., metallic, electrodes can be tuned to predictably manipulate the oxidizing power of surface nitroxide/oxoammonium redox couple, hence showing the practical importance of the electrostatics on the electrolyte side of the radical monolayer. Conversely, for monolayers prepared on the poorly doped electrodes, the electrostatic interactions between the tethered TEMPO units and the semiconductor-side, i.e., space-charge, become dominant and result in drastic kinetic changes to the electroactivity of the radical monolayer as well as electrochemical nonidealities that can be explained as an increase in the self-interaction “a” parameter that leads to the Frumkin isotherm.